Concurso público para docentes do magistério superior na UFSM: otimizando processos - Ceresa, Cristiane (2013)
Public contests for College professors of Higher Education rely on several details during their applying process. At Federal University of Santa Maria (UFSM), the publication of the Resolution No. 020/2009 modified the regulations of these contests in this institution. Without failing to consider the improvements provided by the publication of this Resolution, this study sought, as the main goal, to propose improvements that may contribute to enhance the operation and appliance of contests. In order to achieve its purpose, this study had four specific objectives: i) to carry out a survey of all public contests for College professor offered by the Institution since the application of the Resolution No. 020/2009, and make a diagnosis of the contests; ii) to map the stages that make the opening and application of the contest for the career at Higher Education at UFSM; iii) to identify the main difficulties and facilities observed during the application of contests from the perspective of the Examination Committee members; iv) to identify the practices adopted by other Federal Institutions of Higher Education regarding the application of contests for professors. This study is inserted in the innovation area in the public administration since it aimed to propose new ways to operationalize processes, seeking to achieve changes and advances that provide better results for the public context. This study is justified since it may contribute with practical suggestions for the improvement of the procedures of contests for professors at UFSM, collaborating with the improvement of the procedures involved. Based on the proposed objectives, the study was classified as descriptive in nature. As a research strategy, we used the case study method having the UFSM as the unit of analysis. This research method was chosen because it is aligned with the proposed objectives and with the question that guided the study. Regarding the way of approaching the problem, we used both the qualitative and quantitative methods. The suggestions and contributions proposed by this research are: i) to create a standard form to be used by the Teaching Departments in all the processes of calling for opening an official announcement to fill the openings; ii) to unify the Minutes of calling for the Examining Committee and of the Minutes of the opening of the public contest; iii) to unify the Minutes of announcing the results of the contest and the Minutes of the final opinion of the Examining Committee; iv) to have a total mapping of the flow of the contest from the origin of the opening to the approval of the result in the Federal Official Gazette; v) to adopt other ways to search openings on the pages of the contests; vi) to make the final checklist of the process a mandatory document; vii) to provide nomination ordinances or letter of calling for applicants on the page of the contest; viii) to develop a software for managing the documentation produced during the contest; and ix) Review and redesign of Manual Guidelines for Tendering for Teachers Teaching in Higher UFSM.